Octocollis, a new genus and Octocollis setosus, a new species of Cetoniinae (Coleoptera: Scarabaeidae) from Queensland, Australia - Moeseneder, Christian H.; Hutchinson, Paul M. (Zootaxa, 2012)
The male of Octocollis new genus and Octocollis setosus new species is described from Queensland, Australia. The species displays primitive cetoniine characters. Octocollis is placed in tribe Schizorhinini (Coleoptera: Scarabaeidae: Cetoniinae). The informal name “Polyholcus setosus” is discussed.